2018
DOI: 10.1016/s2095-3119(18)62038-6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of silicon on photosynthesis of tomato seedlings under water stress

Abstract: Silicon can improve drought tolerance of plants, but the mechanism still remains unclear. Previous studies have mainly concentrated on silicon-accumulating plants, whereas less work has been conducted in silicon-excluding plants, such as tomato (Solanum lycopersicum L.). In this study, we investigated the effects of exogenous silicon (2.5 mmol L-1) on the chlorophyll fluorescence and expression of photosynthesis-related genes in tomato seedlings (Zhongza 9) under water stress induced by 10% (w/v) polyethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 31 publications
3
78
0
2
Order By: Relevance
“…The increased chlorophyll content in the current study upon the application of silicon and biochar under water deficit stress conditions might be associated with improved antioxidant defense and therefore maintained physiological processes such as photosynthesis. Zhang et al [29] have reported that the expression of some photosynthesis-related genes are down-regulated in plants grown under water deficit stress conditions; however, exogenous Si can partly up-regulate their expression. This result suggests that Si plays a vital role in alleviating the effect of water deficit stress by modulating photosynthesis-related genes, regulating photochemical process and promoting photosynthesis [29].…”
Section: Physiological and Yield Traitsmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased chlorophyll content in the current study upon the application of silicon and biochar under water deficit stress conditions might be associated with improved antioxidant defense and therefore maintained physiological processes such as photosynthesis. Zhang et al [29] have reported that the expression of some photosynthesis-related genes are down-regulated in plants grown under water deficit stress conditions; however, exogenous Si can partly up-regulate their expression. This result suggests that Si plays a vital role in alleviating the effect of water deficit stress by modulating photosynthesis-related genes, regulating photochemical process and promoting photosynthesis [29].…”
Section: Physiological and Yield Traitsmentioning
confidence: 99%
“…Zhang et al [29] have reported that the expression of some photosynthesis-related genes are down-regulated in plants grown under water deficit stress conditions; however, exogenous Si can partly up-regulate their expression. This result suggests that Si plays a vital role in alleviating the effect of water deficit stress by modulating photosynthesis-related genes, regulating photochemical process and promoting photosynthesis [29]. Under water stress, photosynthesis in the sunflower plant can be affected by two mechanisms-(a) reduced CO 2 diffusion within the leaf owing to closure of stomata and (b) metabolic inhibition of CO 2 [61].…”
Section: Physiological and Yield Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Solanaceous seedling has categorized as an important model plant in investigating the stress tolerance (Zhang et al, 2018). So, several stress studies have been carried on tomato seedlings such as heat stress (Lyu et al, 2018), water stress (Zhang et al 2018), drought (Bian et al, 2019), salinity (Zhou et al 2019), UV-B stress (Liu et al, 2020), chilling (Dong et al, 2020), and waterlogging (Elkelish et al, 2020). Many strategies could be adapted to overcome these stresses depending on the kind of stress, cultivated plants and its growth stage (Zhou et al, 2020).…”
Section: Tomato As a Model Plantmentioning
confidence: 99%